The family meals imperative and everyday family life: an analysis of children's photos and videos. Issue 1 (1st January 2021) - Lindsay, Jo; Tanner, Claire; Leahy, Deana; Supski, Sian; Wright, Jan; Maher, Janemaree
ABSTRACT: At a time of increasing diversity in family forms and family practices the evening family meal is promoted as an imperative; a straightforward solution to complex social problems such as childhood obesity, family breakdown and depression. In this paper we discuss the challenges faced by families in achieving this imperative on an everyday basis drawing on visual data generated by children from a qualitative research project with 50 diverse families in Victoria, Australia. We demonstrate the complex and messy realities of everyday family food consumption which is shaped by social structures such as gender, work and care interacting with micro level elements such as food preferences and child agency. We argue the family meals imperative is a biopedagogy that should be decentred. We suggest that recognising and supporting diverse modes of family interaction and belonging beyond the shared table may be a more fruitful strategy for promoting public health.